Comparison of the Results of Lateral Anal Sphincterotomy vs Botox Injection in Patients with Chronic Anal Fissure in Terms of Pain - Dev, Kapil; Sarfraz, Khurram; Abdullah, Muhammad; Sindhu, Shaista; Yuvraj, Sanjay Neelam; Kumari, Mehak (Biological and Clinical Sciences Research Journal, 2025)
Chronic anal fissure is a common and painful proctologic condition that significantly impairs quality of life. While lateral internal sphincterotomy (LIS) has been the traditional gold standard treatment, concerns about complications such as faecal incontinence have prompted interest in less invasive options like botulinum toxin (BTX) injection. Objective: To compare the effectiveness of lateral internal sphincterotomy versus botulinum toxin injection in terms of pain relief among patients with chronic anal fissure. Methods: This quasi-experimental study was conducted in the Department of General Surgery at the Combined Military Hospital, Hyderabad, from October 2024 to March 2025. A total of 189 patients meeting the inclusion criteria were enrolled and divided into two groups using an odd-even number allocation method: Group A (LIS; n = 95) and Group B (BTX; n = 94). Baseline pain scores were recorded using the Visual Analogue Scale (VAS). Patients were followed up on day 7, at 1 month, and at 3 months post-intervention to evaluate pain resolution, recurrence, and faecal incontinence. Data were analyzed using SPSS version 25, and p-values <0.05 were considered statistically significant. Results: The median (IQR) age of patients in Group A was 37 (13) years, and in Group B was 38.5 (10) years. At 3 months post-intervention, pain persisted in 5 (5.3%) patients in Group A and in none (0%) in Group B (p = 0.024). Recurrence was observed in 1 (1.1%) patient in Group A compared to 13 (13.8%) in Group B (p = 0.001). Fecal incontinence occurred in 7 (7.4%) patients in Group A and 1 (1.1%) patient in Group B (p = 0.031). Conclusion: Botulinum toxin injection demonstrated superior outcomes compared to lateral internal sphincterotomy in terms of pain relief and reduced risk of fecal incontinence, although LIS was more effective in preventing recurrence. BTX may be considered a safer, less invasive alternative in the management of chronic anal fissure.